historical overview of Geneva’s artificial recharge system and its crisis management plans for future usage - de los Cobos, Gabriel (Environmental earth sciences, 2015)
The artificial recharge of transboundary Genevese groundwater uses treated water from the Arve River to recharge the aquifer. This system has been in place since 1980. Although the system has demonstrated its worth and has helped to offset the excessive use of the 1960s and 1970s by raising the average water levels in the aquifer by more than 6 m, the region is still subject to water supply problems. In 2011, several events took place at the local, regional and even international levels which prompted the committee responsible for the use of the transboundary aquifer to tackle the water problem as a result of two events: the Fukushima accident of March 2011 with its radioactive cloud travelling across the globe and passing over Switzerland, and the drought of 2010–2011 which ravaged a large part of Western Europe. The present article examines the effects of these potential problems and raises the issue of the role of the Genevese aquifer in the provision of drinking water and its artificial recharge as the subjects of a strategic study on water distribution in crisis situations.